2019
DOI: 10.1136/oemed-2019-106063
|View full text |Cite
|
Sign up to set email alerts
|

Impact of legislative reform on benefit access and disability duration in workers’ compensation: an interrupted time series study

Abstract: ObjectivesTo determine the impact of legislative changes to the New South Wales (NSW) workers’ compensation scheme on injured workers access to benefits, insurer claim processing and work disability duration.MethodsPopulation-based interrupted time series study of workers’ compensation claims made in NSW 2 years before and after legislative amendment in June 2012. Outcomes included incidence of accepted claims per 100 000 workers, the median and 75th percentile insurer decision time in days, and the median and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Legislative change may also introduce a collider if it alters compensability thresholds. For instance, we previously found that when New South Wales restricted eligibility to its compensation system in 2012, the claim rate decreased while disability duration increased (49). Such an outcome would be consistent with both a change in the cohort towards more severe and complex injuries and a system that has increased the stressfulness of compensation.…”
Section: Alternative Approachessupporting
confidence: 51%
“…Legislative change may also introduce a collider if it alters compensability thresholds. For instance, we previously found that when New South Wales restricted eligibility to its compensation system in 2012, the claim rate decreased while disability duration increased (49). Such an outcome would be consistent with both a change in the cohort towards more severe and complex injuries and a system that has increased the stressfulness of compensation.…”
Section: Alternative Approachessupporting
confidence: 51%
“…Our recent evaluation of these reforms concluded that they had their intended effect: the number of accepted claims fell by 15%. However the reforms also had unintended effects as insurer claim processing time increased by 20% and the median disability duration by 29% [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Further, injured workers with longer claims that were unaffected by Section 39 would generally be historical claims. Given the substantial effect of the 2012 legislation (of which Section 39 was a part) [ 31 ], such historical claims would likely differ systematically from those affected by Section 39. However, we will use sensitivity analyses to estimate the effects of such biases (described in Sensitivity Analysis ).…”
Section: Methodsmentioning
confidence: 99%
“…We previously observed that workers’ compensation system reform was followed by an increase in claim processing time, 5,6 which is predictive of delayed return to work. 7–9 Longer insurer decision times are also an obstacle to early intervention, which is associated with better outcomes and shorter disability durations.…”
Section: Introductionmentioning
confidence: 97%